Influence of isonicotinic acid hydrazide in the blood picture and liver and kidney function tests - Mendoza Euwing, Carlos (1953)
The incessant research for therapeutic elements that dominate the tuberculosis infection accurately oriented by Robert Koch in 1882 to announce the Physiological Society of Berlin and the scientific world if intermediate isolation of the causative agent Mycobacterium Tuberculous offers us now one of its most promising successes with the synthesis of isonicotinic acid hydrazide "new antituberculosis drugs."